Hubungan HDL, LDL, Apo A, dan Apo B dengan Kejadian Penyakit Jantung Koroner - Ruslim, Welly Hartono; Firmansyah, Yohanes; Santoso, Alexander Halim; Edwin Destra; Gunaidi, Farell Christian; Fajarivaldi, Kresna Bambang (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Coronary heart disease (CHD) in the elderly represents the primary clinical manifestation of atherosclerosis and remains a leading cause of death and morbidity. This cross-sectional study aimed to evaluate the role of High-Density Lipoprotein (HDL), Low-Density Lipoprotein (LDL), Apolipoprotein-A (APO-A), and Apolipoprotein-B (APO-B) in the diagnosis and prevention of CHD among the elderly population. The results demonstrated that both APO-A and HDL were significantly negatively correlated with CHD (r = -0.336, p = 0.008; r = -0.274, p = 0.032), suggesting that higher levels of APO-A and HDL are associated with a lower risk of CHD. Conversely, APO-B and LDL showed a significant positive correlation with CHD (r = 0.411, p = 0.001; r = 0.358, p = 0.005), indicating that elevated levels of APO-B and LDL are linked to an increased risk of CHD. These findings highlight that measuring Apolipoprotein A and B levels may offer more valuable insights into atherosclerotic and cardiovascular risk assessment and may enhance the effectiveness of CHD prevention compared to traditional lipid profiles.